Performance Outcomes of Strategic Management Accounting Information Usage in Malaysia: Insights from Electrical and Electronics Companies - Raman, Nordin; Yuserrie, Zainuddin; Fuad; Rasid, Mail; Noor Kaziemah, Sariman (Elsevier Ltd, 2015)
The current research explored the current progress of strategic management accounting (SMA) information usage within electrical and electronics (E&E) companies operating in Malaysia. It was motivated by the scarcity of empirical attention given to the subject despite the claimed importance placed by SMA advocates. The current research sought to substantiate its propositions through two (2) research objectives. The first objective was to investigate the extent of SMA information usage amongst E&E companies and the second was to explore the outcomes of SMA information usage. Survey method was employed for the data collection purposes. Ninety-seven (97) usable questionnaires were received out of the 595 mailed questionnaires. The result suggested that E&E companies used SMA information to high extent. The result indicated that companies’ extent of SMA information usage found to be significantly related to certain aspects of companies’ performance. The current research has revealed some notable development with regards to SMA. The current result implies that, in Malaysia, SMA has made its progress quite extensively that failed to be reported empirically by fellow researchers. Nonetheless, more work needs to be carried out to set forth the important elements of SMA.